Anisotropic charge trapping in phototransistors unlocks ultrasensitive polarimetry for bionic navigation - Pan, Jing; Wu, Yiming; Zhang, Xiujuan; Chen, Jinhui; Wang, Jinwen; Cheng, Shuiling; Wu, Xiaofeng; Zhang, Xiaohong; Jie, Jiansheng (Nature communications, 2022)
Being able to probe the polarization states of light is crucial for applications from medical diagnostics and intelligent recognition to information encryption and bio-inspired navigation. Current state-of-the-art polarimeters based on anisotropic semiconductors enable direct linear dichroism photodetection without the need for bulky and complex external optics. However, their polarization sensitivity is restricted by the inherent optical anisotropy, leading to low dichroic ratios of typically smaller than ten. Here, we unveil an effective and general strategy to achieve more than 2,000-fold enhanced polarization sensitivity by exploiting an anisotropic charge trapping effect in organic phototransistors. The polarization-dependent trapping of photogenerated charge carriers provides an anisotropic photo-induced gate bias for current amplification, which has resulted in a record-high dichroic ratio of >10 4 , reaching over the extinction ratios of commercial polarizers. These findings further enable the demonstration of an on-chip polarizer-free bionic celestial compass for skylight-based polarization navigation. Our results offer a fundamental design principle and an effective route for the development of next-generation highly polarization-sensitive optoelectronics. The direct linear dichroism photodetection without external optics is crucial for applications. Here, Jie et al. exploit the anisotropic charge trapping in organic phototransistors to achieve the dichroic ratio of 10 4 and to demonstrate a polarizer-free celestial compass for bio-inspired navigation.